Changes in the Levels of Pro-Inflammatory Cytokines in Patients with Generalized Periodontitis and Hypertension, Depending on the Method of Treatment - T. Vicharenko; M. Rozhko (Galician Medical Journal, 2017)
Inflammatory mediators have an important role in the pathogenesis of periodontal disease. One of the leading mediators of the initiation of the pathological process is interleukin-1 (IL-1) – an endogenous pyrogen, a lymphocyte-activating factor. Numerous pro-inflammatory effects of interleukin-1β (IL-1β) occur in synergy with tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6), effects on hematopoiesis, participates in nonspecific anti-infective defense.